PENGETAHUAN TENTANG OSTEOPOROSIS DAN PERILAKU KONSUMSI MAKANAN SUMBER KALSIUM PADA REMAJA DI MTs NEGERI PUNDONG BANTUL YOGYAKARTA - Prastiwi Putri Basuki; Eraime Haryany JP (STIKES Wira Husada Yogyakarta, 2017)
Background: Adolescence is a critical period for peak bone mass formation (Peak Bone Mass) and form habits that can help improve bone health. One of these habits is the consumption of calcium according to the number recommended. Bone mineral mass obtained at the end of growth and development is a major determinant of osteoporosis in the future. Knowledge of osteoporosis is an important predisposing factor for direct consumtion behaviour of adolescents to consume calcium source.Objective: This study aimed to analyze the relationship between knowledge of osteoporosis with calcium sources consumption behaviour. Methods: This study was an observational study with cross sectional design. The population in this study is a student MTs Pundong Bantul Yogyakarta. The total sample of 77 people with the sampling method proportional random sampling. Collecting data using questionnaires.Results: The results of this study demonstrate sufficient knowledge about osteoporosis of 51.9% and consumption behavior of the calcium source is less of 81.8%. Conclusion: There was a significant correlation between knowledge of osteoporosis with calcium consumption behavior with p value 0.007